2015
DOI: 10.1039/c5cp00414d
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a p–n junction in a single layer boron-phosphide

Abstract: Two-dimensional (2D) materials have attracted growing interest due to their potential use in the next generation of nanoelectronic and optoelectronic applications. On the basis of first-principles calculations based on density functional theory, we first investigate the electronic and mechanical properties of single layer boron phosphide (h-BP). Our calculations show that h-BP is a mechanically stable 2D material with a direct band gap of 0.9 eV at the K-point, promising for both electronic and optoelectronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 55 publications
8
54
0
Order By: Relevance
“…The results indicated that the 1:1 compound has a graphene-like structure, which is consistent with previous studies 2527 . For the other compounds, we observed a series of stable 2D layered structures in each compound.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results indicated that the 1:1 compound has a graphene-like structure, which is consistent with previous studies 2527 . For the other compounds, we observed a series of stable 2D layered structures in each compound.…”
Section: Resultssupporting
confidence: 92%
“…BP films have been synthesised on silicon carbide using chemical vapour deposition 24 . Theoretically, all the previously predicted 2D BP structures have been constructed from hexagonal configurations, and all of them have a band gap in the range of 1–1.8 eV 2527 . To date, no 2D material with a band gap larger than 2.0 eV has been reported in the B–P system.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated lattice constants a and b are 3.22 and 5.57 Å, which are very close to those of h-BP monolayer. [42][43][44][45] The bond lengths of B-B, P-P and B-P (see Table 1) are comparable to those of 5 h-BP monolayer (B-P: 1.86 Å), 45 borophene (B-B: 1.62 Å), 46 and phosphorene (P-P: 2.22 Å), 47,48 indicating that the chemical bonds in the borophosphene are strong. Cohesive energy is one of the key factors to evaluate the feasibility of experimental synthesis for the predicted 2D materials, [49][50][51] which is calculated according to the formula of In order to evaluate the stability of borophosphene, phonon spectrum with density of state (DOS) is calculated and shown in Figure 1b.…”
Section: Resultsmentioning
confidence: 81%
“…27 As there is no imaginary frequency in the phonon dispersion relations shown in Figure 1(a)-1(c), the dynamic stability of these BX monolayers is guaranteed. Besides, the in-plane Young's modulus (141.9 N/m, 121.5 N/m, and 90.8 N/m for the BP, BAs, and BSb, respectively) are comparable with that of the MoS2 monolayer 28 and obviously larger than that of the phosphorene, 29 indicating the mechanical stability of these systems. Moreover, we see from the insets of Fig.…”
mentioning
confidence: 88%